Clinical outcomes related to the incidence of ventilator-associated pneumonia in adults - a cohort study - Viana, Ariane Aparecida; Rosa, Déborah Maciel Cavalcanti; Ambrozin, Alexandre Ricardo Pepe; Andrade, Renata Croce Megna; Jamami, Maurício; Martinelli, Bruno (Pontifícia Universidade Católica do Paraná, 2018)
AbstractIntroduction: Ventilator-Associated Pneumonia (VAP) is a common complication found in the Intensive Care Unit (ICU) and is associated with increased mortality, length of hospital stay and mechanical ventilation (MV) time.Objective: To determine the incidence of VAP and its impact on the clinical course of the subject undergoing invasive MV in the ICU.Methods:This is a cohort study of hospitalized subjects in the general adult ICU of the State Hospital of Bauru / SP. The clinical information for the period of 19 months were collected. Stratification for the groups was based on the presence or absence of VAP, free_VAP and VAP, respectively. The Hotelling T² with 95% confidence, chi-square and the Mann-Whitney tests were executed using the R software and the results showed as mean ± standard deviation and absolute and relative distribution (p < 0.05).Results:The sample was of 322 subjects; the VAP group consisted of 73 (22.67%), 54.79% male, age: 62.31±16.96 years and the APACHE II: 29.98 ± 8.64. The VAP group had longer time of the MV and of the ICU compared to free VAP group; even in this group, the highest incidence of death in the ICU occurred between the 16th and 20th day of hospitalization. The free VAP group was older and 50% of the patients discharged from hospital.Conclusion: VAP and their interfaces still impact on the clinical evolution of the subjects mainly on the time factor of MV and ICU stay. The highest incidence of death in the ICU occurs in the first weeks.

ResumoIntrodução: A Pneumonia Associada à Ventilação Mecânica (PAV) é uma complicação comumente encontrada na Unidade de Terapia Intensiva (UTI) e está associada à maior mortalidade, tempo de internação e ventilação mecânica (VM).Objetivo: Verificar a incidência da PAV e seu impacto sobre a evolução clínica dos sujeitos submetidos à ventilação mecânica invasiva na UTI.Métodos: Trata-se de um estudo de coorte com sujeitos internados na UTI geral adulto do Hospital Estadual de Bauru/SP. Foram coletadas as informações clínicas referentes ao período de 19 meses. A estratificação para os grupos foi realizada com base na ocorrência ou não da PAV, sem_PAV e PAV, respectivamente. Foi aplicado o teste T2 de Hotelling com 95% de confiança e Qui-Quadrado utilizando o Software “R” e os resultados apresentados em média ± desvio padrão e distribuição absoluta e relativa (p < 0,05).Resultados: A casuística foi de 322 sujeitos; o grupo PAV constou de 73 (22,67%), sendo 54,79% do sexo masculino, idade: 62,31 ± 16,96 anos e APACHE II: 29,98 ± 8,64. O grupo NAV teve maior tempo de VM e na UTI se comparado ao grupo sem_NAV; ainda neste grupo, a maior incidência de óbito na UTI ocorreu entre o 16° ao 20° dia de internação. O grupo sem_PAV era mais velho e 50% deste tiveram alta hospitalar.Conclusão: A PAV e suas interfaces ainda causam impacto sobre a evolução clínica dos sujeitos principalmente quanto ao fator tempo de ventilação mecânica e de internação na UTI. A maior incidência de óbito na UTI ocorre nas primeiras semanas.
Desfechos clínicos ligados à incidência de pneumonia associada à ventilação mecânica no adulto - estudo de coorte
Keywords: Ventilator-Associated Pneumonia; Pulmonary Medicine; Cohort Studies; Pneumonia Associada à Ventilação Mecânica; Pneumologia; Estudos de Coortes